2019
DOI: 10.1634/theoncologist.2018-0794
|View full text |Cite
|
Sign up to set email alerts
|

High IDO1 Expression Is Associated with Poor Outcome in Patients with Anal Cancer Treated with Definitive Chemoradiotherapy

Abstract: Despite increased incidence of anal squamous cell carcinoma (ASCC), treatment recommendations have remained unchanged for the past 35 years. This article profiles the tumor microenvironment of patients with localized ASCC, examining CD8, PD‐1, PD‐L1, IDO1 and HLA class I expression and, specifically, characterizes expression of IDO1 in the context of several key components of the immune microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…High IDO expression, like NOS2 and COX2, predicts poor outcome [90,[96][97][98]. Given that IDO is a heme protein, it is susceptible to redox regulation.…”
Section: Tryptophan and N-formylkynureninementioning
confidence: 99%
“…High IDO expression, like NOS2 and COX2, predicts poor outcome [90,[96][97][98]. Given that IDO is a heme protein, it is susceptible to redox regulation.…”
Section: Tryptophan and N-formylkynureninementioning
confidence: 99%
“…IDO1 is interferon-induced and has been shown to mediate powerful immunosuppression in cancer. Growing evidence indicates that IDO1 is overexpressed in the vast majority of solid tumors and associated with clinical prognosis, such as anal ( 18 ), esophageal ( 19 ), as well as cervical cancer ( 20 ). More importantly, several molecular drugs targeting IDO1 have been evaluated in multiple clinical trials with encouraging results ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in the United States revealed that advanced T stage and immune marker e.g. tumour indoleamine 2,3 dioxygenase 1 (IDO 1) could be used as predictor of recurrence [25].…”
Section: Introductionmentioning
confidence: 99%